The Budget Software Pro-Forma for Aiding Equipment Procurement Commitees’ Decission in Manufacturing and Non-Manufacturing - Akinnuli, Basil Olufemi (European Journal of Scientific Exploration, 2018)
Equipment Committee is put in place in many industries with memorandum of understanding. Frequently it is difficult to hit the bull. The cause is the lacked knowledge of this service. Hence, development of a software pro-forma using experience and the research data of the experts aids the Equipment Procurement Committee as per their decision making. This was achieved by identification of the required strategic decisions of equipment procurement, ascertaining acceptable mathematical forecasting model fit for this type of budgeting. There were developed: spread sheets for data analysis and storage, the required logic of acting (graphically linking the spread sheets), forecast purchase pro-forma and actual purchased pro-forma, Visual Basic Excel program (Budget Analyzer) that lead to the model application for results generation using a case study. The Forecasted Budget for this case study is N53,740.00; Actual Purchase N46,023,750.00; while Budget Variance is N7,716,670.57. Since this is positive value, this shows an over-budget of 16.77%. This amount needs to be retired by the purchaser otherwise it may lead to embezzlement. This model will find its application in all industries affected by equipment procurement, their activities in both developing and developed countries.